Nepal Scale up Chlorhexidine as Part of Essential Newborn Care: Country Experience - Lamichhane, Bikash; Khanal, Leela; Shrestha, Parashu Ram; Dawson, Penny; Singh, Samikshya (Journal of Nepal Health Research Council, 2018)
Chlorhexidine is a broad-spectrum antiseptic, effective on gram positive and gram negative bacteria as well as some viruses, having strong skin binding effect. Randomized controlled trials conducted in South Asian countries have proven that the use of chlorhexidine (4% weight/weight) for cord care can reduce neonatal mortality and prevent severe cord infections. Between 2011 and 2017, Nepal completed nationwide scale-up of the use of chlorhexidine by integrating with ongoing maternal and neonatal health programs, under the leadership of the Child Health Division. The chlorhexidine coverage and compliance study (2017) has revealed that the country has achieved 59% coverage of the intervention to date, with lowest use among home births. The strategy should be further strengthened to ensure that every newborn in need is reached with chlorhexidine.